MULTIPLE TASK TYPES IN IELTS WRITING - D. Sh. Tirkashev (Galaxy International Interdisciplinary Research Journal, 2022)
This article suggests crucial tips to complete writing task 1 in IELTS exam as the applicants may face difficulties dealing with describing line graph and pie chart. Some structures and essential vocabularies are introduced as well to lessen the hardship in writing task of IELTS.